Enhancing Palm Kernel Oil Refining: Synergistic Effects of Hydrogen Peroxide and Bentonite Clay on Bleaching Efficiency - O. U. Osazuwa; O. J. Oghenehwosa; C. C. Afamuefunah; J. E. Ossai; O. A. Osadolor (Journal of Applied Sciences and Environmental Management)
Optimizing the refining process of palm kernel oil, particularly its bleaching phase, is crucial for removing free fatty acids and impurities. This study investigates the synergistic effects of hydrogen peroxide (H2O2) and bentonite clay on palm kernel oil bleaching using a two-stage refining process. Key findings indicate that pre-treating with H2O2 before clay application yields optimal results at 90 ℃ with a 2: 1.5 H2O2-to-bentonite ratio. Notably, H2O2 pre-treatment effectively removes free fatty acids, albeit with a slight increase in moisture content. Further optimization using Response Surface Methodology (RSM) with Box-Behnken Design revealed optimal reaction conditions of temperature: 98.7°C, H2O2 volume: 19.763 mL, bentonite clay amount: 9.868 g, and contact time: 22.681 mins. These predicted optimal values demonstrate significant potential for industrial application and future research, enhancing the efficiency and quality of palm kernel oil refining.